Wykluczenie dobra sakramentu, dobra wiary oraz dobra potomstwa po stronie pozwanej, a także wykluczenie dobra potomstwa po stronie powodowej (kan. 1101 § 2 KPK) w wyroku Roty Rzymskiej c. Bottone z 2 lutego 2010 roku - Dzierżon, Ginter (Ius Matrimoniale, 2020)
In the presented study the Author commented on the judgment of the Roman Rota c. Bottone of 2 February 2010. The analysis shows that the legal part of the rotal judgment was based on the general theory of a legal act. In the factual part ponens accumulated two titles exclusion of the good of the sacrament and exclusion of the good of faith. The invalidity of the marriage was proven using indirect proof. In the present case, it has been shown that what prompted the defendant to take such a step was the fact that even before the marriage she had maintained a relationship with another man. It was also proved that the plaintiff's exclusion of offspring was in close connection with the defendant's change of attitude towards him.